2011
DOI: 10.1063/1.3601475
|View full text |Cite
|
Sign up to set email alerts
|

Bending a periodically layered structure for transformation acoustics

Abstract: Anisotropic acoustic metamaterials have been proved very useful for their high potential in guiding and manipulating sound energy. In this paper, we further develop the idea by using periodically layered structures for transformational acoustics. Such a simple scheme periodically inserts identically bent solid plates in a background fluid. It forms a metamaterial with high refractive index normal to the curved plates and an index near to one along the plates. We show that the periodically layered structure, co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In practice, a homogeneous anisotropic metamaterial can be conveniently mimicked by using periodically layered structure. 5,18 In the current work, we will demonstrate an implementation of the proposed scheme by using a fin-like structure, which can mimic a metamaterial with extremely anisotropic parameters. 5 The designed model is composed of fins placed periodically at the angular direction in the host medium (chosen as air here), as shown in Fig.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…In practice, a homogeneous anisotropic metamaterial can be conveniently mimicked by using periodically layered structure. 5,18 In the current work, we will demonstrate an implementation of the proposed scheme by using a fin-like structure, which can mimic a metamaterial with extremely anisotropic parameters. 5 The designed model is composed of fins placed periodically at the angular direction in the host medium (chosen as air here), as shown in Fig.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Similar to an invisibility cloak that can conceal isolated objects as if nothing is present in the space, a carpet cloak hides a bump below it and renders the uneven surface flat to observers. Although some previous work demonstrated that employing anisotropy is a possible route as well [34][35][36], we focus on isotropic design as most authors have done [11,[37][38][39][40][41][42][43]. Taking advantage of the light-fluid analogy, the principle of cloaking can be interpreted with a very intuitive picture, that light is guided to wrap around an object like water flows around a stone [2,27].…”
Section: A 2d 'Airfoil' and 'Magnus' Carpet Cloakmentioning
confidence: 99%